2018
DOI: 10.1002/gps.4872
|View full text |Cite
|
Sign up to set email alerts
|

Using dolls for therapeutic purposes: A study on nursing home residents with severe dementia

Abstract: This study suggests that DT is a promising approach for reducing BPSD in people with dementia, supporting evidence emerging from previous anecdotal studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 33 publications
1
31
0
19
Order By: Relevance
“…Reasonably this could be related to anognosia among person with advanced dementia (54). There are several means to improve the sense of wellbeing among persons with advanced dementia such as using multisensory stimulation for example including music and massage (88), singing (89), dancing (90), animals (91) and dolls (92). Listening to well-known songs or music and to positive stories from their own lives can strengthen the feeling of being important.…”
Section: Strengthening Self 3 Communionmentioning
confidence: 99%
“…Reasonably this could be related to anognosia among person with advanced dementia (54). There are several means to improve the sense of wellbeing among persons with advanced dementia such as using multisensory stimulation for example including music and massage (88), singing (89), dancing (90), animals (91) and dolls (92). Listening to well-known songs or music and to positive stories from their own lives can strengthen the feeling of being important.…”
Section: Strengthening Self 3 Communionmentioning
confidence: 99%
“…Despite some staff and family members viewing dolls as patronising or infantilising (Hubbard & Olsen, 2016;Braden & Gaspar, 2015;Shin, 2015;Hahn, 2015;Mitchell & Templeton, 2014;James, Mackenzie, & Mukaetova-Ladinska, 2006;Alander, Prescott, & James, 2015), all 12 articles agreed regarding the positive impact of offering dolls to care home residents with dementia, including: improved communication and social interaction (Ng, Ho, Koh, Tan, & Chan, 2017;Mitchell, McCormack, and McCance, 2016;Alander et al 2015;Shin, 2015;Bisiani & Angus, 2013;Cohen-Mansfield, Marx, Dakheel-Ali, Regier, and Thein, 2010); reduced anxiety (Alander et al 2015;Bisiani & Angus, 2013); and reduction in behavioural and psychological symptoms of dementia (Cantarella, Borella, Faggian, Navuzzi, & De Beni, 2018). Mitchell et al (2016) reported an improvement in eating, however, Cantarella et al (2018) did not. Dolls also provided a tangible object to be cared for, offering companionship and a sense of connectedness and inclusion (Alander et al 2015), and reducing loneliness (Bisiani & Angus, 2013).…”
Section: Dollsmentioning
confidence: 99%
“…Ta kriterij je izpolnjevalo 10 člankov (Tabela 2), ki smo jih razvrstili po lestvici hierarhije dokazov, kot to priporočata Melnyk in Fineout-Overholt (2011). Ena raziskava je bila randomizirana (Cantarella, et al, 2018), štiri raziskave so bile opazovalne študije, (James, et al, 2006;Ellingford, et al, 2007;Braden & Gaspar, 2015;Shin, 2015), pet je bilo opisnih oziroma kvalitativnih raziskav (Tamura, et al, 2001;Fraser & James, 2008;Bisiani & Angus, 2013;Heathcote & Clare, 2014;Alander, et al, 2015). Glede na geografsko porazdelitev so bili vključeni članki iz Amerike (n = 1), Koreje (n = 1), Japonske (n = 1), Avstralije (n = 1) in Evrope (n = 6).…”
Section: Ocena Kakovosti Pregleda In Opis Obdelave Podatkovunclassified
“…Orodje zajema 19 kriterijev, ki se ocenjujejo z nominalno lestvico (Pluye, et al, 2013). Štiri raziskave so bile ocenjene z maksimalno oceno 100 % (Fraser & James, 2008;Braden & Gaspar, 2015;Shin, 2015;Cantarella, et al, 2018), ena raziskava je bila ocenjena s 75 % (Alander, et al, 2015), pet raziskav z najnižjo oceno, 25 % (Tamura, et al, 2001;James, et al, 2006;Ellingford, et al, 2007;Bisiani & Angus, 2013; Heathcote & Clare, 2014; ). Nobene raziskave nismo izključili zaradi slabe metodološke ocene.…”
Section: Ocena Kakovosti Pregleda In Opis Obdelave Podatkovunclassified